1998
DOI: 10.1091/mbc.9.10.2839
|View full text |Cite
|
Sign up to set email alerts
|

cut11+: A Gene Required for Cell Cycle-dependent Spindle Pole Body Anchoring in the Nuclear Envelope and Bipolar Spindle Formation inSchizosaccharomyces pombe

Abstract: The "cut" mutants of Schizosaccharomyces pombe are defective in spindle formation and/or chromosome segregation, but they proceed through the cell cycle, resulting in lethality. Analysis of temperature-sensitive alleles of cut11 ϩ suggests that this gene is required for the formation of a functional bipolar spindle. Defective spindle structure was revealed with fluorescent probes for tubulin and DNA. Three-dimensional reconstruction of mutant spindles by serial sectioning and electron microscopy showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
197
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 159 publications
(205 citation statements)
references
References 64 publications
6
197
0
2
Order By: Relevance
“…This inference is corroborated by a reduction in the percentage of azygotic asci with greater than four spores to near wild type levels (Table 3). Also, microscopy of zygotes formed early in the cross of klp2⌬,dhc1-d1 with itself, with the use of either DAPI to visualize the nuclei or strains carrying Cut11p-GFP to mark the nuclear envelopes (West et al, 1998) revealed that zygotes with a single nucleus were rare in this cross. Most contained two nuclei whose morphology resembled that of diploid nuclei during the "horsetailing" motions of meiotic prophase ( Figure 4C; Chikashige et al, 1994).…”
Section: CL Troxell Et Almentioning
confidence: 96%
See 3 more Smart Citations
“…This inference is corroborated by a reduction in the percentage of azygotic asci with greater than four spores to near wild type levels (Table 3). Also, microscopy of zygotes formed early in the cross of klp2⌬,dhc1-d1 with itself, with the use of either DAPI to visualize the nuclei or strains carrying Cut11p-GFP to mark the nuclear envelopes (West et al, 1998) revealed that zygotes with a single nucleus were rare in this cross. Most contained two nuclei whose morphology resembled that of diploid nuclei during the "horsetailing" motions of meiotic prophase ( Figure 4C; Chikashige et al, 1994).…”
Section: CL Troxell Et Almentioning
confidence: 96%
“…A complete replacement of the klp2 ϩ by ura4 ϩ was made by a singlestep gene replacement protocol (Rothstein, 1991), with the use of a cassette containing two genomic regions flanking the either side of the klp2 ϩ gene and ura4 ϩ as the selectable marker. A 2900-nt PstIHindIII fragment corresponding to the sequence Ϫ2900 to Ϫ68 nt upstream of the klp2 ϩ ORF was subcloned into the PstI-HindIII site of the bacterial cloning vector pSPORT1 (GIBCO BRL), which had been modified to carry the ura4 ϩ gene (pSPORT1-URA4; West et al, 1998). A 1.3-kb BglII-HindIII fragment corresponding to the sequence ϩ83 nt to ϩ1043 nt downstream of the klp2 ϩ ORF was blunt-ended and subcloned into the KpnI site of pSPORT1-URA4 with the aid of KpnI linkers.…”
Section: Disruption Of Klp2 ؉mentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments with GFP-tagged genes were generally done at 25°C, and others were done at the temperatures noted. Fixed cells were prepared for tubulin and DNA staining with the use of a double aldehyde method (Hagan and Hyams, 1988), and antibodies were applied as previously described (West et al, 1998). DNA staining was also done with cells fixed by adding 1/10 volume of cell culture to methanol at Ϫ20°C for 2-15 min.…”
Section: Microscopymentioning
confidence: 99%